Cover Picture: Group 9 Metal Complexes of meso‐Aryl‐Substituted Rubyrin (Chem. Eur. J. 30/2015). Issue 30 (20th July 2015) - Soya, Takanori; Osuka, Atsuhiro
<x xml:space="preserve">Abstract</x> Metalations of meso‐aryl‐substituted rubyrin with CoII, RhI, and IrIII give non‐twisted Hückel conformations, as shown by T. Soya and A. Osuka in their Communication on page 10639 ff. The bis‐CoII complex displays antiaromatic character, whereas the bis‐RhI complex and mono‐IrIII complexes exhibit aromatic characters, despite their highly distorted conjugated networks. The CoII complex also shows antiferromagnetic coupling between two CoII ions via the bridging acetoxy groups.